Assessing the knowledge of trainee residents for liver involvement and related issues in COVID-19 pandemic - Qadeer, Muhammad Ali; Abbas, Zaigham; Asim, Muhammad; Ali, Shoukat; Altaf, Abeer (Asian Journal of Medical Sciences, 2021)
Background: Regular educational activities have suffered since the start of COVID-19 pandemic. New data has been emerging regularly regarding COVID-19 and the optimal way of care for patients with COVID-19 infection. Emphasis upon dispensing knowledge in current pandemic times should be made. Aims and Objective: We assessed the knowledge of internal medicine and gastroenterology trainees regarding liver involvement and related issues in the current COVID-19 pandemic. Materials and Methods: This online survey comprised of 10 questions designed to examine the basic knowledge of Sars-Cov-2 virus, knowledge regarding liver involvement in COVID-19, and the ability to decide on patient care. Results: A total of 100 responses were collected. Most of the responses were from Pakistan (n=75). More than 80% of trainees responded correctly regarding the accurate indication of endoscopic procedures during COVID-19 pandemic, absence of ACE-II receptor expression on astrocytes, upper respiratory secretions being an eligible sample for SARSCOV- II, avoiding regular outpatient follow up, avoiding hydroxychloroquine as a prophylactic drug, and azithromycin in decompensated cirrhosis, continuing beta-blockers and lactulose in a decompensated patient, melena being an accurate indication for screening endoscopy and the choosing right set of PPEs. Less than 50% of responders knew correctly regarding NAFLD being a notorious factor for COVID-19 related complications, ACE-II receptor expression by cholangiocytes and enterocytes, saliva and stool being an eligible sample for SARS-COV-II detection, palliative approach as an appropriated management step for decompensated-CLD patients and history of ascites as an appropriate indication for screening endoscopy. GI trainees performed better in some areas of knowledge. Conclusions: Trainees were updated in many aspects of the recent guidance in the management of COVID-19 but there were many lacunae in the knowledge. So, continuous medical education activities are essential to keep the residents updated about the changing developments in the management of COVID-19.